Baseline Interleukin-10, CD163 and Tumor Necrosis Factor-like Weak Inducer of Apoptosis Gingival Tissue Levels in Relation to Clinical Periodontal Treatment Outcomes : A 12-Week Follow-up Study - Yilmaz Mustafa; Demir Esra; Gürsoy Mervi; Firatli Erhan; Gürsoy Ulvi Kahraman (United Kingdom, 2022)
Background: The aim of this study was to examine the relationship between healing response after non-surgical periodontal treatment and baseline gingival tissue levels of M2 macrophage activation-related proteins CD163, interleukin (IL)-10, interferon (IFN)-γ, and tumor necrosis factor-like weak inducer of apoptosis (TWEAK), and the CD163/TWEAK ratio.
Methods: Eighty-eight gingival tissue samples from 44 Stage III/IV, Grade C periodontitis patients (18 smokers) and 41 tissue samples from 41 periodontally healthy participants (18 smokers) were evaluated. Clinical parameters were recorded in periodontally healthy individuals at baseline and in periodontitis patients at pre-treatment and 2, 6, and 12 weeks following therapy. IL-10, IFN-γ, CD163, and TWEAK levels were analyzed with Luminex technique.
Results: Tissue levels (median, 1st -3rd quartile) of IL-10 (pg/ng protein), CD163 (pg/μg protein) and TWEAK (pg/μg protein) were as follows: IL-10 periodontitis: 2.08, 0.86-5.32 and periodontally healthy: 5.22, 3.20-10.25; CD163 periodontitis: 8.85, 4.92-14.06 and periodontally healthy: 18.36, 12.51-34.02; TWEAK periodontitis: 0.08, 0.05-0.11 and periodontally healthy: 0.16, 0.12-0.21. IL-10, CD163, and TWEAK levels were higher (P < 0.001) in periodontally healthy tissues than in periodontitis tissues. Pocket closure at 12 weeks was associated with elevated baseline gingival CD163 levels (P = 0.047) and CD163/TWEAK ratio (P = 0.001). Elevated baseline gingival CD163/TWEAK ratio was associated with pocket reduction at 6 (P = 0.022) and 12 weeks (P = 0.002).
Conclusion: Associations of pocket closure with pre-treatment gingival tissue CD163 levels and CD163/TWEAK ratio indicate that baseline M2 macrophage activation profile may play a role in periodontal wound healing.